Investigation on the Structure and Electrochemical Properties of La-Ce-Mg-Al-Ni Hydrogen Storage Alloy - Yuqing Qiao; Jianyi Xi; Minshou Zhao; Guangjie Shao; Yongchun Luo; Limin Wang (Journal of Chemistry)
Structure and electrochemical characteristics of La0.96Ce0.04Mg0.15Al0.05Ni2.8 hydrogen storage alloy have been investigated. X-ray diffraction analyses reveal that the La0.96Ce0.04Mg0.15Al0.05Ni2.8 hydrogen storage alloy consisted of a (La, Mg)Ni3 phase with the rhombohedral PuNi3-type structure and a LaNi5 phase with the hexagonal CaCu5-type structure. TEM shows that the alloy is multicrystal with a lattice space 0.187 nm. EDS analyse shows that the content of Mg is 3.48% (atom) which coincide well with the designed composition of the electrode alloy. Electrochemical investigations show that the maximum discharge capacity of the alloy electrode is 325 mAh g−1. The alloy electrode has higher discharge capacity within the discharge current density span from 60 mA g−1 to 300 mA g−1. Electrochemical impedance spectroscopy measurements indicate that the charge transfer resistance RT on the alloy electrode surface and the calculated exchange current density I0 are 0.135 Ω and 1298 mA g−1, respectively; the better eletrochemical reaction kinetic of the alloy electrode may be responsible for the better high-rate dischargeability.